Presynaptic modulation by neuromedin U of sensory synaptic transmission in rat spinal dorsal horn neurones - Moriyama, Maiko (Blackwell Science Inc, 2004)
Neuromedin U (NMU) is a brain–gut peptide first isolated from the spinal cord. Recent studies on NMU and its receptors have suggested a role of NMU in sensory transmission. Here we report on the localization of NMU in sensory neurones, and the actions of NMU in the substantia gelatinosa (SG) and the deep layer of the dorsal horn (laminae III–V) in adult rat spinal cord slices using the patch-clamp technique. An immunohistochemical study revealed that NMU peptide was present in most of the dorsal root ganglion neurones. In the spinal cord, NMU-immunoreactive neurones were located in the deep layer (laminae III–V), but not in the SG. However, NMU-positive axon terminals were observed in the SG as well as the deep layer. Bath-applied NMU (10 μm) increased the frequency, but not amplitude, of miniature excitatory postsynaptic currents (mEPSCs) in the SG and deep layer neurones by 146 ± 14% (P < 0.01, n = 17) and 174 ± 21% (P < 0.01, n = 6), respectively, without inducing any postsynaptic membrane currents recorded in tetrodotoxin. On the other hand, NMU did not affect miniature inhibitory postsynaptic currents recorded in tetrodotoxin. These findings, taken together, suggest that NMU acts on the presynaptic terminals of the primary afferent fibres working as an autocrine/paracrine neuromodulator to increase mEPSC frequency of the SG and deep layer neurones. This may account for the spinal mechanisms of the NMU-induced hyperalgesia reported previously.